1983
DOI: 10.1093/jn/113.7.1346
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of Zinc by the Rat Ileum: Effects of Histidine and Other Low-Molecular-Weight Ligands

Abstract: The role of certain amino acids, dipeptides and organic acids as ligands to facilitate the intestinal absorption of zinc was investigated by using an in vivo procedure on ileal segments of adult rats. Ligand:zinc ratios equal to or less than 3:1 were optimal for amino acids and dipeptides such as L-glutamate, glycine, L-histidine, L-tryptophan and glycylglycine. An excess of ligand reduced zinc absorption. At a 130:1 L-histidine:zinc ratio the absorption of zinc was less than one-fourth that obtained at a 3:1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(34 citation statements)
references
References 21 publications
3
29
1
1
Order By: Relevance
“…Increasing intakes of dietary protein are associated with enhanced absorption,13 and it is believed that AAs that are released during digestion may play an important role in maintaining zinc solubility in the intestine, therefore aiding absorption 31. In rats, His enhances the absorption of zinc at a maximal rate at near physiological pH 32. In the present study, Arg was associated by linear regression to plasma zinc concentrations, and this association is consistent with the proposed role of AA.…”
Section: Discussionsupporting
confidence: 90%
“…Increasing intakes of dietary protein are associated with enhanced absorption,13 and it is believed that AAs that are released during digestion may play an important role in maintaining zinc solubility in the intestine, therefore aiding absorption 31. In rats, His enhances the absorption of zinc at a maximal rate at near physiological pH 32. In the present study, Arg was associated by linear regression to plasma zinc concentrations, and this association is consistent with the proposed role of AA.…”
Section: Discussionsupporting
confidence: 90%
“…The inhibition observed with increasing peptide concentrations can be explained in terms of the peptide/Zn2+ ratio and saturation of the peptide transporter. Several authors obtained similar results with amino acids presenting a high affinity for zinc such as histidine and cysteine (Wapnir, Khani, Bayne & Lifshitz, 1983;Wapnir & Stiel, 1986;Wapnir, Lee & Stiel, 1989;Gachot, Tauc, Morat & Poujeol, 1991;Aiken, Horn & Saunders, 1992). They showed that zinc can 'follow' the amino acid through its specific carrier (i.e.…”
Section: Discussionmentioning
confidence: 72%
“…medium was about 30 pmollpg D a A/h, in very good pmollpg DNA/ I T for our substrate concentration of 5 nM A large number of ligands have been proposed to serve as substrates for Zn uptake. These range from prostaglandin (Song and Adham, 1976), citric acid (Lonnerdal et al, 19801, metallothionein (Richards and Cousins, 1975), and histidine (Wapnir et al, 1983) in the gut, and prostaglandin (Evans andJohnson, 1977, citric acid (Hurley et al, 1979), and lactoferrin (Blakeborough et al, 19831, in human milk, and even a ZnHCO, carrier in red cells (Torrubia and Garay, 1989). Furthermore, Zn uptake by leucocytes and 3T3 cells is reduced in the presence of plasma and amino acids (Jones et al, 1981;Schwartz and Matrone, 1975).…”
Section: Time (Min)mentioning
confidence: 99%